PEMBERDAYAAN POTENSI WISATA PANTAI BUMI TAKA KELURAHAN SUNGAI PARIT MELALUI PROMOSI DIGITAL DAN EDUKASI KESELAMATAN PENGUNJUNG - Era Wahyuningsih; Intan Sophia; Lilipia (SEPAKAT Sesi Pengabdian pada Masyarakat, 2026)
Pantai Bumi Taka is a local tourism destination located in Sungai Parit Subdistrict that has natural potential to be developed as a driver of the local community’s economy. However, the management of this destination still faces challenges, particularly the limited use of digital promotion and the low level of awareness regarding visitor safety. This program aimed to empower tourism managers and the surrounding community through strengthening digital-based promotion and providing visitor safety education. The methods employed included field observation, semi-structured interviews with tourism managers and local business actors, as well as educational activities. The results indicated an improvement in managers’ understanding of the importance of digital promotion and the implementation of tourism safety, as reflected in the emergence of initiatives to utilize digital media and to provide safety information media within the tourist area. This program contributes to strengthening the capacity of community-based tourism management and supports the development of more independent and sustainable local tourism.